Archaeological excavations in prehistoric sites of the Blue Nile area, Central Sudan. Excavaciones arqueológicas en yacimientos prehistóricos del Nilo Azul, Sudán Central - Jimeno, Alfredo; Menéndez, Mario; Fernández, Víctor M. (Complutum, 2003)
Extensive excavations were carried out in two Mesolithic sites, in the river area (Sheikh Mustafa-1, radiocarbon dated to c. 7930-7600 bp) and in the Wadi Soba zone (El Mahalab, c. 7705-6940 bp), and at a wadi Early Neolithic site (Sheikh el Amin, c. 5555-4590 bp). The results of comprehensive analysis of stratigraphical conditions, pottery and lithic material and other cultural types are presented. Multivariate methods such as principal component and rotated factor analysis have been applied to quantitative data from excavated sectors and squares at the three sites. Even though the Mesolithic sites are partially deflated, significant information was gathered on the cultural evolution in the area during the 8th – 5th millennia bp. The inferred scenario presents several change trends: from specifically Nilotic pottery decoration (incised wavy line) to Saharan types such as impressed rocker and dotted wavy line, from lithic backed points and narrow lunates, used for fishing and hunting big game, to wide lunates for the hunting of smaller game. Fishing importance decreased along the whole period of the three sites. Plant gathering, deduced from grinders frequency, increased to a maximum during the Neolithic but a decrease is inferable for the latter phases of this period when the transition begun to a pastoralist way of life.